2003
DOI: 10.1046/j.1523-1755.2003.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Cux-1 transgenic mice develop glomerulosclerosis and interstitial fibrosis

Abstract: These observations indicate that increased expression of Cux-1 in mesangial cells results in cell proliferation and mesangial expansion. In addition, these changes are potentially related to disruption of podocyte architecture leading to loss of filtration. These results suggest that expression of Cux-1 is sufficient to induce the early events of mesangioproliferative glomerulonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Transgenic mice expressing the full-length p200 CUX1 protein under the control of a cytomegalovirus promoter had striking multi-organ hyperplasia and organomegaly 15 . Further characterization of these mice revealed glomerulosclerosis and interstitial fibrosis in the kidney 59 , and hepatomegaly was associated with inflammation and biliary cell hyperplasia 60 . Expression of the full-length p200 CUX1 protein under the control of the mouse mammary tumour virus long terminal repeat (MMTV-LTR) led to the development of mammary tumours of diverse histopathological types with a long latency and a penetrance of 21% (REF.…”
Section: Interstitial Fibrosismentioning
confidence: 99%
“…Transgenic mice expressing the full-length p200 CUX1 protein under the control of a cytomegalovirus promoter had striking multi-organ hyperplasia and organomegaly 15 . Further characterization of these mice revealed glomerulosclerosis and interstitial fibrosis in the kidney 59 , and hepatomegaly was associated with inflammation and biliary cell hyperplasia 60 . Expression of the full-length p200 CUX1 protein under the control of the mouse mammary tumour virus long terminal repeat (MMTV-LTR) led to the development of mammary tumours of diverse histopathological types with a long latency and a penetrance of 21% (REF.…”
Section: Interstitial Fibrosismentioning
confidence: 99%
“…The first transgenic mouse models displayed various cancer-associated disorders depending on the specific isoform and tissue type expression. The lesions included multi-organ organomegaly, glomerulosclerosis and interstitial fibrosis, progressively cancerous lesions in the liver, and myeloproliferative-disease-like myeloid leukemias (Ledford et al, 2002;Brantley et al, 2003;Vanden Heuvel et al, 2005;Cadieux et al, 2006). That altered CUX1 expression or activity may play a causal role in myeloproliferative disorders received additional support from the recent identification of a missense mutation (V1288L) within the Cut homeodomain of CUX1 in a case of secondary acute leukemia (AML) with preceding myeloproliferative neoplasms (MPN), although the functional consequence of this mutation has yet to be investigated (Thoennissen et al, 2011).…”
Section: Transgenic Mouse Models Demonstrate a Causal Role Of Cux1 Inmentioning
confidence: 99%
“…Indeed, p27 kip1 expression was reduced in the kidney of CUX1 transgenic mice and reporter assays demonstrated that CUX1 was able to repress transcription from the p27 kip1 gene promoter (Ledford et al, 2002). Adult mice eventually developed glomerulosclerosis as a result of increased mesangial cell proliferation, interstitial fibrosis, and proteinuria (Brantley et al, 2003). In contrast to the situation in the kidney, hepatomegaly was associated with a decrease in p21 Cip1 , but not p27 Kip1 , expression (Vanden Heuvel et al, 2005).…”
Section: Cux1 Transgenic Mouse Modelsmentioning
confidence: 99%